Pengaruh Pembelajaran Ekspositori terhadap Prilaku Moral Anak Usia Dini - Baidarus; Radhiyatul Fithri (Universitas Lancang Kuning, 2023)
Moral education in elementary school students is very much needed to be done by teachers because it is the moral development of students that shapes and guides a person in later life. The aim of this study was to find out and analyze the influence of expository learning on the moral behavior of students in the 1st grade at SD Muhammadiyah I Pekanbaru by using quasi-experimental method. The population of this study was the 1st grade of SD Muhammadiyah I Pekanbaru with 48 students, which consisted of 24 students in the control class and 24 in the experiment class. Based on the results of the comparative analysis paired samples T test, the comparison of values before treatment and after treatment was -4,480. At the significance levels of 0,05 and df 23, a t-table of 2,069 was obtained. So, t count was (4,480) < t table (2,069) and significance value were (0,000) < α (0,05), then Ho is rejected. It means that expository learning has an influence on the moral behavior of students in 1st grade at SD Muhammadiyah I Pekanbaru.